“Un livre scandaleux et diffamatoire”: Militant Translations of the Discours de la servitude volontaire - Emmenegger, Camilla; Gallino, Francesco; Gorgone, Daniele (TTR)

(untitled) (Association canadienne de traductologie, 2021)
The Discours de la servitude volontaire boasts a long tradition of militant translations. We argue that these translations—whose introductions and paratextual materials often aim to enlist La Boétie to a specific political cause or ideology—must be taken into account when analyzing the Discours’ political content. As Miguel Abensour (2006) pointed out, the Discours’ elusive complexity fulfills a performative function, whose goal is to reveal the reader’s conception of freedom. It can be compared to a gamebook, in which most translators, editors and/or commentators get involved when publishing the text: they make particular interpretative choices and offer their specific reading of La Boétie’s thesis. In order to illustrate this peculiar interpretative dynamic, we briefly examine three case studies: an Italian (1944), an American (1942) and a Soviet (1952) translation. All three contain a strong political message and, we suggest, each of these messages brings to light a new path through La Boétie’s gamebook, developing a new vision of his intentionally paradoxical political theory.